Flexible thermoplastic starch films functionalized with copper particles for packaging of food products - Lopez, Olivia Valeria (2020)
Biodegradable films based on thermoplastic corn starch (TPS) and copper particles with antimicrobial capacity were developed. Copper nanoparticles (Cu) and silica coated copper microparticles (Si-Cu) in the range of 0.25 to 5% were used. Composite films were obtained by melt-mixing and subsequent thermo-compression. Particles distribution within TPS matrix and the presence of some pores and cracks, induced by Si-Cu particles, was evaluated by SEM. The presence of both fillers gave composite films a brown pigmentation and decreased their transparency; these effects were more pronounced at higher particles concentrations. Regarding mechanical properties, copper particles at 1 and 5% acted as reinforcing agents increasing the maximum tensile strength but their presence lead to a decrease in elongation at break, affecting films ductility. Composites inhibited the growth of Gram+ and Gram- bacteria, demonstrating their antimicrobial capacity. Copper effectively migrated to a simulant of aqueous foods and naked particles concentration in the simulant medium resulted higher than the minimum inhibitory concentration for bacteria. The characteristics and properties of developed composite films make them an interesting material for food primary packaging, mainly for meat fresh products.